REKONSTRUKSI VISI DAN KURIKULUM BARU PENDIDIKAN TINGGI ISLAM - Hasbi Indra (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
Islamic higher of Education are born in colonialism era at 1944, set by community of islamic teacher at West Sumatera. The first after colonialism of Dutch and Japan and proclamation of Indonesia by Soekarno-Hatta its are established by Hatta and Natsir the Islamic higher of education at Jakarta in wich named ADIA, and also the following yearsin Yogyakarta established PTAIN. And 1960 ADIA and PTAIN are both merger and benamed IAIN as centres of institution in Jakarta and Yogyakarta. The Instituions until now still exist and in globalization era and MEA are face crusial challenges ahead. Its era are development of science and technology (IPTEK), such as in fields of medicine and others and to has great benefits for humanity, for their needs. But, also there are the side negativeit makes people becoming trapped in the